The impact of anabolic-androgenic steroids used by athletes on cardiovascular system - Borecki, Rafał; Słowikowska-Hilczer, Jolanta; Jegier, Anna; Zdrojewski, Tomasz; Domińczak, Dominika; Szadkowska, Iwona (Journal of Medical Science, 2026)
Introduction. In many countries, the use of anabolic-androgenic steroids (AAS) has become increasingly common among individuals who engage in physical activity and wish to improve their body composition with particular influence on increasing muscle mass. This phenomenon affects not only professional sports competitors but also amateur athletes and recreational exercisers. Easy access to these preparations, both through online sales and illegal trade, encourages the widespread use of AAS, despite their well-documented adverse health effects. With regard to the cardiovascular system, these substances may cause many pathological changes leading to the development of hypertension, myocardial ischemia, heart failure or the occurrence of sudden cardiac death. The mechanisms underlying these processes are multidirectional, on the one hand resulting from direct structural damage to the heart and blood vessels, and on the other hand indirectly inducing lipid disorders or prothrombotic processes.Material and methods. A comprehensive literature review was conductes usuing PubMed and Google Scholar databases to identify studies investigating the impact of AAS on the cardiovascular system Keywords covered “anabolic-androgenic steroids”, “cardiovascular risk”, “myocardial hypertrophy”, and “AAS abuse”.Results. This review synthesizes current knowledge on the multidirectional pathophysiological mechanisms of AAS. Although the available scientific evidence alearly indicates a significant cardiovascular risk associated with these substances, the detailed molecular pathways have not yet been explained.Conclusions. The aim of the study was to inform clinicians and healthcare providers about the significant cardiovascular risks associated with AAS use, which is becoming an increasing health problem in clinical practice.
Keywords: testosterone; anabolic-androgenic steroids; cardiovascular system; myocardial infarction; heart failure; sudden cardiac death